Noise Predictive DFE for Single Carrier W-LAN Systems with Frequency Domain Equalization - Koppler, Alois; Springer, Andreas; Weigel, Robert (Asia-Pacific Microwave Conference (APMC), 2002)
In this contribution we extend our previously presented single carrier transmission scheme with frequency domain equalization (SC/FDE) to hybrid equalization in the frequency domain and in the time domain. The proposed structure, which deploys low complexity frequency domain equalization in the feedforward part and time domain noise predictive decision feedback equalization (NP-DFE), allows us to add decision feedback to conventional single carrier block by block transmission with a cyclic prefix. Our results indicate that conventional hard decision feedback rather decreases than increases the performance of an SC/FDE system in combination with channel coding.
elib2cris::1512001600,koppler2002a